(untitled) (Annals of Medical Research, 2025)
Aim: It is known that apelin-13 is one of the major neuropeptides with a clear and crucial role in the circuits that are involved in mood disorders. In the development and/or maintenance of pathological anxiety, abnormalities of the hippocampus and amygdala play an important role. Here, we assessed the potential anxiolytic effect of apelin-13 on anxiety-like behaviors in male rats. Materials and Methods: A total of 48 male Wistar rats were divided into 4 groups (n=12). Control (C), Social Isolation (SI), Apelin-13 (A), and Social Isolation + Apelin-13 (SI+A). In the C and A groups, four animals in each cage for 8 weeks. In the SI and SI+A groups, each animal was housed individually for 8 weeks. After that apelin-13 administration was applied by osmotic pomp. Anxiety/depression-related behaviors were evaluated using the Elevated Plus Maze (EPM), Open Field Test (OFT), and Light-Dark boxes (LDB). We also measured the expression of Apelin-13, Apelin receptor (APJ), Brain Derived Neurotrophic Factor (BDNF), Mammalian Atonal Homolog 1 (MASH1), Nestin, Doublecortin (DCX) and Neuritin in the hippocampus. These are important markers indicating the anxiety mechanism in the hippocampus. Results: The results of our study showed that apelin-13 administration reduced anxiety behaviors. Open arm entires and time spent were higher in the A group. In the open field test, grooming and rearing were lower in the SI group. Moreover, apelin-13 and APJ gene expression was higher in the A group. Conclusion: The results of the study indicate that apelin-13 infusion may lead to a decrease in anxiety-related behaviors in male rats.